A MODEL OF HUMAN RESOURCE COLLABORATION AND INTEGRATION IN THE IMPLEMENTATION OF THE REPRESENTATIVE FUNCTION OF THE HOUSE OF REPRESENTATIVES OF THE REPUBLIC OF INDONESIA - Jazuli Juwaini (POLITEKNIK LP3I JAKARTA, 2026)
The implementation of the representative function of the House of Representatives of the Republic of Indonesia (Dewan Perwakilan Rakyat Republik Indonesia—DPR RI) constitutes one of the fundamental pillars of constitutional democracy, aimed at ensuring that public aspirations are effectively incorporated into the public policymaking process. The increasing complexity and dynamic nature of societal issues require that the representative function no longer relies solely on the individual capacities of members of parliament, but also on the effectiveness of collaboration and integration among the human resources (HR) supporting the constitutional duties of the legislative institution. This study aims to analyze the significance of human resource collaboration and integration in strengthening the representative function of the DPR RI through a qualitative case study conducted at the Secretariat General of the DPR RI. The findings reveal that the effectiveness of the representative function is strongly influenced by the synergy among members of parliament, expert staff, civil servants, researchers, policy analysts, legislative drafters, librarians, and other supporting units in producing comprehensive information, policy analyses, and recommendations. Nevertheless, the study also identifies persistent organizational fragmentation, sectoral ego, and suboptimal knowledge integration, which limit the effectiveness of institutional support for the representative function. Accordingly, this study proposes a collaborative model based on knowledge sharing, cross-unit coordination, and human resource capacity development to establish a more adaptive, responsive, and evidence-based support system for parliamentary representation. Strengthening human resource collaboration is therefore a fundamental prerequisite for improving the quality of the DPR RI's political representation in responding to the demands of modern democracy.